Effect of Social Skills Training on Self Concept of Teenage Mothers, A case study of Training College in Kenya - okore, Chinyere; Asatsa, Stephen; Ntarangwe, Maria (Innovation Journal of Social Sciences and Economic Review, 2021)
The purpose of this study was to investigate the effectiveness of social skills training in enhancing the self-concept of teenage mothers in Kibera, a population often marginalized and vulnerable due to societal stigma, rejection, and isolation following teenage pregnancy. The study employed a mixed-method sequential explanatory design, anchored on Carl Rogers' person-centered theory and Bandura's social cognitive theory. The research targeted 150 teenage mothers, collecting quantitative data through self-concept and social skills questionnaires, and qualitative data through interviews with a social worker and a school administrator. Quantitative data was analyzed using SPSS version 21, and participants with low mean scores in self-concept were further examined through qualitative methods. The findings revealed that social skills training significantly improved the self-concept of teenage mothers, providing them with tools to better manage their emotions and interactions. The qualitative analysis underscored the psychological and emotional challenges these mothers face, particularly the lack of support and acceptance from their families. The study concludes that enhancing self-concept in teenage mothers requires not only social skills training but also increased psychological support and familial acceptance. The implications of this study suggest the need for stronger guidance and counselling services for both parents and teenage mothers. It also emphasizes the importance of policy interventions in low-income communities, particularly in education, to reduce the incidence of teenage pregnancy and its associated challenges. Addressing these issues holistically could lead to better outcomes for teenage mothers, empowering them to rebuild their lives and improve their futures.
Keywords: Training on Social Skills; Self-Concept; Teenage Mothers; Training College; Kenya.